HUMAN CAPITALTRAINING PROGRAM FOR SELF-AWARENESS - Manowattana, Chadchawan; Watthanabut, Busakorn; Chavasirikunthol, Nantana; Siribhuripalangkorn, Kunpravee (Journal of MCU Social Science Review, 2020)
The objectives of this research article were to study the current condition, the basic elements of the training program for self-awareness and to develop a human capital training program for self-awareness. The qualitative research methodology was used in this study by using In-depth-interview (Semi-Structured) to collect data from 15 key informants and analyzed data using the content descriptive analysis technique and synthesized the common character and conclusion. Findings were that: the current condition of the human capital development regarding that the human is the primary resource to drive organization to success by starting analysis of the internal factors of the organization, such as the vision, mission, and core values of the organization. Including the potentials of human capital and the external factors of the organization should also be considered, such as the economics, social, and political conditions and the most important was the advancement of technology. The basic elements of the human capital training program for self-awareness were: 1. Personnel in organization knowledge acquire, 2. Mindfulness, 3. Shared Vision, 4. Team Learning, 5. Thinking system of personnel in organization. Besides, the study also was found that the process of human capital training program development for self-awareness was the heart of organizational development. If the personnel and staffs in the organization had positive attitude, commitment and the sense of belonging and the part of the ownership of the organization, this would yield the efficiency to the operation of the organizations.